Consumer response to monochrome Guideline Daily Amount nutrition labels. (May 2015) - Boztuğ, Yasemin; Juhl, Hans Jørn; Elshiewy, Ossama; Jensen, Morten Berg
Highlights: We analyse the impact of GDA nutrition label introduction on purchase behaviour. We use supermarket scanner data from two food categories: yogurt and ready meals. Attraction/market share decreases for unhealthier products after label introduction. Results show no generalizable change in choice behaviour after label introduction. Price and habit have a larger impact on purchase behaviour than label introduction. Abstract: Front-of-pack (FOP) nutrition labelling has received extensive political attention in recent years. Most studies assessing the influence of nutrition labelling focus on consumer attention to labels, while few concentrate on its effects on actual purchase behaviour. In this study, we present results from an analysis of scanner data provided by a large UK retailer. We focus on two food categories, using store-brand products that are labelled with a front-of-pack, monochrome Guideline Daily Amount (GDA) nutrition label. The analyses are based on models at both an aggregated and disaggregated level to enable us to identify as many influencing factors on food choice as possible. We utilize the SSAg/1 health score for our food categories as a dependent variable to obtain an objective measure of healthiness. Our results suggest that the GDA label introduction reduces attraction of unhealthier products in terms of market share but does not affect product choice behaviour. Instead, price and habit exhibit a greater impact on purchase behaviour and product choice than the GDA label introduction.